Analisis Pola Aktivitas Mahasiswa Lulus Tepat Waktu bebasis Data Mining dan Process Mining (Studi Kasus Program Studi Sistem Informasi Fakultas Ilmu Komputer Universitas Brawijaya) - Hafizh Yuwan Fauzan; Nanang Yudi Setiawan; Ahmad Afif Supianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
One of many problems at Information System at Faculty of Computer Science Universitas Brawijaya is that there is some undergraduate who have not graduated even though they have passed 8th semester. This can affect the accreditation assessment, because if students drop out due to reaching the semester limit then it will affect the accreditation assessment. For this very reason, initial steps are needed that can make students graduate on time. The solution offered in this study is to create a cluster, based on academic attributes. After that, Process Mining is performed in each cluster so that information and relationships that cannot obtained in the data. This research will use K-Means ++ algorithm for Data Mining and Fuzzy Miner algorithm for Process Mining. The results of the clustering process are four clusters obtained with their respective characteristics, and also for each of these clusters can be seen statistical information and models process of the thesis.